Ultrasound as a diagnostic tool fir fetal nuchal cord during labor - Palacios, Miguel (2015)
OBJETIVE: To compare the diagnostic ability of abdominal ultrasounito detect fetal nuchal cord. DESIGN: Clinical analytical study. MATERIAL AND METHODS: Fifty-seven term pregnant patients in labor had abdominal ultrasound (US) on admission in order to identify fetal nuchal cord and compare such finding with outcome at delivery or cesarean-section (gold standard). RESULTS: Nuchal cord prevalence diagnosed by ultrasound was 21,1%, with 80% sensitivity (CI 95% 72,7 to 87,3), 96% specificity (CI 95% 92,9 to 99,1), and positive and negative predictive values of 87% and 94%, respectively. Test accuracy was 92%.McNemar's discordance analysis between obstetric US and gold standard was not significant (p=0,7236) and the likelihood ratios for positive and a negative results were 20 and 0,20, respectively. CONCLUSIONS: US study during labor for diagnosis of fetal nuchal cord had high specificity (96%) and appears to be a good screening test for nuchal cord identification in high risk pregancies.